Delayed occluder displacement following patent ductus arteriosus closure successfully managed with thoracic endovascular aortic repair: a case report and literature review - Dihao Pan; Anfeng Yu; Chengcheng Li; Liangwei Chen; Chengyao Ni; Haige Zhao (Journal of Cardiothoracic Surgery)
Abstract Interventional occlusion of Patent ductus arteriosus (PDA) is generally efficacious and complications such as delayed occluder displacement are infrequent. Herein, we report a case of 24-year-old female with a history of unsuccessful PDA closures, who subsequently experienced delayed occluder displacement into the left main pulmonary artery. Despite numerous unsuccessful catheter-based interventions, thoracic endovascular aortic repair (TEVAR) was successfully executed. This procedure effectively resolved the PDA without any postprocedural complications. This case highlights the efficacy and safety of TEVAR as a viable alternative for managing complex PDA cases involving occluder displacement.